Uji Aktivitas Antijamur Saccharomyces cerevisiae terhadap Phytophthora palmivora Penyebab Busuk Buah Kakao - Gargita, I Wayan Diksa; Khalimi , Khamdan; Pranatayana, Ida Bagus Gde (AGRICA, 2024)
The fungus Phytophthora palmivora is a phytopathogen that can cause cocoa pod rot disease. This work was conducted to determine the antifungal activity of Saccharomyces cerevisiae against P. palmivora ATCC39039 and identify the antifungal compounds produced by S. cerevisiae. The antifungal activity test of S. cerevisiae against P. palmivora ATCC39039 was performed using the dual culture method. Determination of the antifungal activity of S. cerevisiae extract on the growth of P. palmivora ATCC39039 was carried out using the poisoned food technique. The results indicated that S. cerevisiae successfully provided an inhibitory effect on the growth of P. palmivora ATCC39039 fungal colonies with an inhibition percentage of 92.93%. S. cerevisiae extract was also successful inhibiting the growth of P. palmivora ATCC39039 fungal colonies with the percentage inhibition ranging from 92.36% to 97.60%. S. cerevisiae extract contains thirteen compounds that have antifungal activity, namely Ethyl alcohol, 2-Methylbutan-1-ol, Isopentyl alcohol, Benzyl Carbinol, 1,2-Ethanediol, Acetoxyethane, 4-Hydroxyphenethyl alcohol, 4,4-Dimethyloxazolo, Acetoin, 2-Bromotetradecanoic acid, Dodecane,1-chloro, Octanoic acid ethyl ester, dan Diethylhexylphthalate. The results of this work provide information that S. cerevisiae can be utilized as a biological agent to control cocoa pod rot disease.